DAMPAK PEMBELAJARAN BERBASIS MASALAH (PBL) TERHADAP PENGEMBANGAN KETERAMPILAN PEMECAHAN MASALAH SISWA PADA MATA PELAJARAN MATEMATIKA - Muhammad Furqan (Majelis Pendidikan Aceh, 2023)
The objective of this study is to look into the effectiveness of instructional videos using the Problem-Based Learning Method in developing problem-solving skills in primary school students. To improve students' problem-solving skills, this study incorporated instructional material related to math topics